Evaluación del efecto pulguicida del extracto de hojas y raíces de la flor de gallinazo (Tagetes erecta) en disoluciones de 50 % Y 100% contra la pulga (Ctenocephalides spp) In vitro en el municipio de Popayán - Castillo Salazar, Juan José; Gómez Ortega, Andrés Felipe (Universidad Antonio Nariño, 2022)
The resistance of the flea (Ctenophalides spp), in the face of traditional pharmacological treatments, has been presented in recent years as a great problem for canine owners, since infestations in canines become very serious causing problems of Allergic flea bite dermatitis (DAPP), taking this into account, the initiative has been taken to control the flea infestation called pulicosis, with an alternative and innovative treatment, which was carried out with the extract of the gallinazo flower (Tagetes erecta ) at different concentrations, in fleas collected from canines and placed in vitro, in order to determine their insecticidal effect by means of sprays, which were managed in a descriptive experimental design in randomized 3 x 3 blocks where each experimental unit will be a Petri dish with 10 fleas to be evaluated. To evaluate the insecticidal effect, three treatments will be taken into account, which will be divided as follows: 1) Treatment 0: placebo (water). 2) Treatment 1: 50% extract, 3) Treatment 2: 100% extract In order to carry out the treatments, the fleas were extracted using a special comb and the fleas were placed in a urine sample bottle. They were taken to an airtight box that was made of transparent acrylic and had two holes in which I had a pair of latex sleeves to facilitate handling and avoid possibly escaping one of the fleas (ctenophalides spp), in this airtight box it was made the manipulation of fleas, to place them in each experimental unit which had an environment similar to its habitat in the dog, this was achieved by placing a bed of dead fur in each experimental unit; The fur was obtained from a canine which had not been treated for this problem 8 months ago. It was carefully placed in each experimental unit with the 10 fleas and thus the spraying of its respective treatment was carried out to verify its insecticidal effect Each experimental unit had a technical sheet and a label to identify it, so the continuous monitoring of the fleas will be carried out, the time is averaged in minutes, where the time it took for the extract to make its insecticidal effect was taken into account The plant was grown in a controlled environment (home planting) as follows: sowing was carried out in pots made of wood, natural fertilizer was added to the pots, the seeds that were sown 1cm deep, 11 which were in the process of growth and it was waited about 3 months for them to flower, since this plant does not have many requirements to be cultivated, planting at home was facilitated. In this way we obtained the raw material for the research. To obtain the extract of the Gallinazo Flower (Tagetes erecta), the soxhelt method was carried out and thus we obtained the stock solution that was worked in solutions at different concentrations. "Soxhlet extraction consists of the successive washing of a solid mixture with a certain solvent (ethanol) that" washing or extracting "the most soluble components in it from the mixture. By successively washing a mixture, it is possible to extract components whose solubility in the extracting solvent is very low, due to the accumulated effect of multiple extractions. The vegetable extract obtained is the result of concentrating the active principles of the plants, these must be toxic to pests, which, because they are biodegradable, cause minimal damage to the ecosystem. Due to these aspects, it is necessary to design and optimize the working conditions of a liquid solid extraction equipment in such a way that its handling is accessible to all types of people and its construction is economical, to obtain quality products and thus satisfy the needs of this sector” (Caldas, 2012, p. 1).